The drafter ebook - Harrison, Kim (The Peri Reed Chronicles, 2015)
The Bourne Identity meets Minority Report in this "truly wild ride" ( RT Book Reviews ) set in a futuristic Detroit—the first in #1 New York Times bestselling author Kim Harrison's Peri Reed Chronicles. Peri Reed is a Drafter—a special ops agent with the unique ability to jump back forty seconds in time when missions go wrong. But this skill allows her partner, who is responsible for replacing her memory of events, to feed her false memories and set her up as a corrupt agent. Working with Silas, a broody, intriguing psychologist trying to bring Opti corruption to light, Peri begins to piece her twisted reality together as she flees the organization she once trusted implicitly. Peri is caught: rebuilding the memory of the night she killed her partner risks her sanity and in trying to put an end to Opti, she is only getting closer to the very faction that wants to see her dead. Can she get her revenge, or will her tenuous grip on reality leave her vulnerable all over again?